Street Vendor Regulation Enforcement in Keputran Market Surabaya by Satpol PP - Pratama, Edo Pandu; Tukiman, Tukiman (Journal of Management and Administration Provision, 2024)
Street Vendors (PKL) play a significant role in Indonesia's informal economy, although their presence often conflicts with the government regarding the use of public spaces. In cities like Surabaya, the government seeks to regulate PKL activities through local regulations enforced by the Municipal Police (Satpol PP), aiming to create a more orderly and cleaner urban environment. However, these efforts often face resistance from PKL, who feel their livelihoods are being threatened. This study aims to examine and describe the implementation of the policy for controlling street vendors by the Satpol PP of Tegalsari District in the Keputran Market area of Surabaya. The research employs a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. Data analysis is conducted using an interactive analysis technique involving data collection, data reduction, data presentation, and conclusion drawing. The results show that communication, resources, and bureaucratic structure indicators support the policy implementation, but the disposition indicator is not yet optimal due to the lack of full support from the implementers, thus requiring improvements to enhance policy effectiveness.